Influence of the Dissolution of Al- and Zn-Based Galvanic Anodes on the Composition of Calcareous Deposits - Florent Batisse; Malo Duportal; Céline Rémazeilles; Alban Edouard; Ludovic Meuriot; Philippe Refait (Journal of Marine Science and Engineering, 2025)
The possible incorporation of Al and Zn issuing from galvanic anodes in the calcareous deposit forming on carbon steel surfaces subjected to cathodic protection was studied via three methodological approaches. The calcareous deposits were analyzed by X-ray diffraction for phase composition and X-ray fluorescence spectroscopy for chemical composition. First, a calcareous deposit formed on the steel pile of a seaport installation, sampled far (2 m) from the closest galvanic anode, was found to incorporate a small amount of the pollutants present in the seawater (Zn, Ti, Cu). An in situ experiment performed at another seaport focused on the calcareous deposit formed on steel surfaces close to the anode. In this case, a small amount of Zn directly issuing from the anode was incorporated in the deposit. This amount remained low as it corresponded to Zn(II) species adsorbed on the surface of aragonite crystals. Finally, laboratory experiments were performed with Zn(II) and/or Al(III) chlorides (10−3 mol L−1 each) added to seawater. With both Zn(II) and Al(III), a Zn(II)-Al(III) hydroxychloride precipitated in the bulk seawater. With only Al(III), and under a higher cathodic current density, Al(III) could be incorporated in a deposit mainly composed of brucite, but only in small amount.